1995
DOI: 10.1159/000119223
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of the Extended or Ancestral Haplotype B44-SC3O-DR4 in Autism

Abstract: Autism likely results from several different etiologies or a combination of pathological mechanisms. Recent studies suggest that this disorder may be associated with immune abnormalities, pathogen-autoimmune processes and perhaps the major histocompatibility complex (MHC). In a preliminary study we found that 22 autistic subjects had an increased frequency of the extended or ancestral MHC haplotype B44-SC3O-DR4. The current study attempted to confirm this observation by studying 23 additional randomly chosen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 12 publications
2
54
0
1
Order By: Relevance
“…Further studies found that several HLA haplotypes, in particular HLA-DR4, occur more often in children with ASD than in the general population. 32,33,36,37 The HLA genes are located within a large genomic region referred to as the major histocompatibility complex (MHC). This region contains numerous other genes, including the complement protein C4 gene (C4A; alias C4B), which is important for innate immunity.…”
Section: Autoimmunity and Immune Dysfunction In Individuals With Asdmentioning
confidence: 99%
“…Further studies found that several HLA haplotypes, in particular HLA-DR4, occur more often in children with ASD than in the general population. 32,33,36,37 The HLA genes are located within a large genomic region referred to as the major histocompatibility complex (MHC). This region contains numerous other genes, including the complement protein C4 gene (C4A; alias C4B), which is important for innate immunity.…”
Section: Autoimmunity and Immune Dysfunction In Individuals With Asdmentioning
confidence: 99%
“…In addition to genes related to specific neurotransmitter systems and to factors that directly regulate gene expression, recent studies have suggested that genes within the major histocompatibility complex (MHC, or HLA in humans), on chromosome 6p21.3, may encode predisposing factors in autism [253,78,252] (but see [197]). Genes in this region encode products that are required for self-nonself recognition by the adaptive immune system.…”
Section: Immunological Signallingmentioning
confidence: 99%
“…Genes in this region encode products that are required for self-nonself recognition by the adaptive immune system. In particular, an unusual number of people with autism may share all or part of the extended MHC haplotype B44-SC30-DR4 [253,78,252,232]. Evidence also exists for a link between autism and a null allele of the C4B gene, in the class III MHC region, [254], and correspondingly low levels of C4b protein [249] which is essential in activation of the classical complement pathway.…”
Section: Immunological Signallingmentioning
confidence: 99%
“…A possible role of the HLA genes has also been proposed for other neurological disorders such as autism (5). Besides, it has been singled out that an HLA extended haplotype A2-B44-DR4 occurs with increased frequency in autism (9). The involvement of HLA-DR4 in autism spectrum disorder (ASD) has also been confirmed by the transmission disequilibrium test (TDT) that linked DR4 allele to ASD through the paternal chromosome (10).…”
Section: Discussionmentioning
confidence: 99%